A chimeric design of heterospin 2p–3d, 2p–4f, and 2p–3d–4f complexes using a novel family of paramagnetic dissymmetric compartmental ligands. Issue 48 (1st June 2017) - Patrascu, Andrei A.; Calancea, Sergiu; Briganti, Matteo; Soriano, Stéphane; Madalan, Augustin M.; Cassaro, Rafael A. Allão; Caneschi, Andrea; Totti, Federico; Vaz, Maria G. F.; Andruh, Marius
Abstract : Original end-off bicompartmental ligands bearing a nitronyl–nitroxide arm have been designed for synthesizing various heterospin molecular systems. Abstract : End-off bicompartmental ligands bearing a nitronyl–nitroxide arm have been designed for synthesizing various heterospin molecular systems. These ligands can selectively interact with 3d and 4f metal ions, leading to 2p–4f, 2p–3d, and 2p–3d–4f complexes. The magnetic properties of the 2p–4f and 2p–3d–4f complexes have been investigated and rationalized by theoretical calculations.